2008
DOI: 10.1143/apex.1.124002
|View full text |Cite
|
Sign up to set email alerts
|

Ti-mask Selective-Area Growth of GaN by RF-Plasma-Assisted Molecular-Beam Epitaxy for Fabricating Regularly Arranged InGaN/GaN Nanocolumns

Abstract: The Ti-mask selective-area growth (SAG) of GaN on Ti-nanohole-patterned GaN templates by rf-plasma-assisted molecular-beam epitaxy was employed to demonstrate the fabrication of regularly arranged InGaN/GaN nanocolumns. The SAG of GaN nanocolumns strongly depended on the growth temperature (Tg); at Tg below 900 °C, no SAG occurred, but above 900 °C, SAG occurred. However, an excessive increase in Tg to above 900 °C at a nitrogen flow rate (QN2) of 3.5 sccm brought about increased inhomogeneity in the nanocolum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
189
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(199 citation statements)
references
References 21 publications
10
189
0
Order By: Relevance
“…72,76 The GaN nanorods were selectively grown on patterned 5 nm Ti/GaN/sapphire templates. The holes in the Ti mask layer were opened by focused ion beam etching.…”
Section: A Mbe Growthmentioning
confidence: 99%
“…72,76 The GaN nanorods were selectively grown on patterned 5 nm Ti/GaN/sapphire templates. The holes in the Ti mask layer were opened by focused ion beam etching.…”
Section: A Mbe Growthmentioning
confidence: 99%
“…A possible route can be found in the selective area growth ͑SAG͒ of MBE GaN NWs on patterned substrates, even though only few studies have been so far reported. [24][25][26][27] We demonstrate in this letter a method to obtain regular arrays of GaN NWs via SAG on a patterned Si mask. The study of SAG is relevant on the one hand for device applications, which require the control over the NW positioning and on the other hand for offering valuable information about the adatom kinetics of the NW growth process.…”
mentioning
confidence: 99%
“…Figure 3b shows a bright-field scanning TEM image of a GaN nanocolumn supporting bending nanoplates. The azimuthal incidence angle was [11][12][13][14][15][16][17][18][19][20]. Figure 3d shows the arrangements of Ga and N atoms in the N-polarity and Ga-polarity GaN crystals.…”
Section: Methodsmentioning
confidence: 99%
“…The growth mechanism has been discussed in detail in previous studies. 1,12,13 Note that these nanocrystals could not be fabricated by crystal growth without the Ti film, namely the growth directly on the N-polarity GaN layer did not realize such nanocrystals. In addition, the TEM images suggested that the supporting GaN nanocolumns of the nanoumbrellas did not include dislocations such as those reported for Ga-polarity GaN nanocolumns.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation